The important of service quality towards customer satisfaction at Menara Taming Sari / Siti Khadijah Abu Bakar - Abu Bakar, Siti Khadijah (2008)
This research is about a study of the important of service quality towards customer satisfaction at Menara Taming Sari Melaka by analyzing five dimension of service quality. These dimensions are include the tangible, reliability, responsiveness, assurance and empathy are the dimensions that used to identify in order to investigate whether or not these factor exists in order to achieved customer satisfaction at Menara Taming Sari Melaka. The data are obtained from the observation and the personal interview with the Customer Services Assistant at Menara Taming Sari Melaka. The findings shows that most of the dimensions of the service quality gives an impact to customer satisfaction because satisfaction of customers came from good service quality. Based on the observation and personal interview with the staff, it was conclude that most of the customers that come to the Menara Taming Sari Melaka are satisfied with the service quality and there are some of the dimensions of the services need to improve in order to give fully customer satisfaction and bring positive word of mouth. Based from the findings, there are some of the dimensions need to be improve so that can achieved customer satisfaction towards the service quality provided.